EMI in the Saudi Arabian context - Khulod Aljehani; Marko Modiano (Springer, 2024)
Abstract The Kingdom of Saudi Arabia (KSA) has recently made significant changes to its tertiary education programs, aligning itself with other nations in the Middle East and North Africa by adopting the practice of English Medium Instruction (EMI). However, EMI is not without drawbacks. In the UAE and Qatar, for example, researchers have reported on the potential adverse consequences of the policy. This study seeks to explore KSA university students' and instructors' attitudes toward EMI, with a significant focus on broader social and cultural perceptions, while also addressing pedagogical issues. This approach contrasts with the predominant focus in the existing literature, which primarily emphasizes pedagogical aspects. A mixed-method approach is utilized in which students were surveyed quantitatively, and instructors were interviewed. The study does not reveal any evidence of broader social and cultural concerns such as those reported elsewhere; however, the findings do indicate student resistance to a monolingual approach, whether English or Arabic. Thus, by taking into consideration the findings presented here and in other studies, in conjunction with relevant theoretical suppositions, this study substantiates the benefits of a mixed-medium approach combining English and Arabic.